P53-dependent hypusination of eIF5A affects mitochondrial translation and senescence immune surveillance - Jiang, Xiangli; Baig, Ali Hyder; Palazzo, Giuliana; Pizzo, Rossella del; Bortecen, Toman; Größl, Sven; Zaal, Esther A.; Amaya Ramirez, Cinthia; Kowar, Alexander; Avilés Huerta, Daniela; Berkers, Celia R.; Palm, Wilhelm; et al. (Nature Communications, 2024)
Cellular senescence is characterized by a permanent growth arrest and is associated with tissue aging and cancer. Senescent cells secrete a number of different cytokines referred to as the senescence-associated secretory phenotype (SASP), which impacts the surrounding tissue and immune response. Here, we find that senescent cells exhibit higher rates of protein synthesis compared to proliferating cells and identify eIF5A as a crucial regulator of this process. Polyamine metabolism and hypusination of eIF5A play a pivotal role in sustaining elevated levels of protein synthesis in senescent cells. Mechanistically, we identify a p53-dependent program in senescent cells that maintains hypusination levels of eIF5A. Finally, we demonstrate that functional eIF5A is required for synthesizing mitochondrial ribosomal proteins and monitoring the immune clearance of premalignant senescent cells in vivo. Our findings establish an important role of protein synthesis during cellular senescence and suggest a link between eIF5A, polyamine metabolism, and senescence immune surveillance.